Methodology for manufacturing cranial implants from DICOM images and CAD/CAM/CNC technologies (2005)
This article proposes a methodology for the design and manufacture of cranial implants from DICOM images and CAD / CAM / CNC technologies. This methodology is based on the Computerized Axial Tomography (CT) of the patient's head, with which the three-dimensional reconstruction of the skull is carried out. Then, in the CAD system the implant is reconstructed by varying the technique used depending on the region of the skull with defect or trauma. Once the model is obtained, the assembly is designed and the implant is manufactured with support in CAM / CNC technology.